KEBERTERIMAAN PENGGUNAAN SISTEM WEBSITE WEGO TERHADAP PEMBELIAN TIKET ELEKTRONIK - , ALDIYANA HERDANU; , Dr. Sumiyana, M.Si, Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Titles in this study is the \"Acceptance Use Website WEGO system to purchase electronic tickets\". This study aims to identify and find empirical evidence on user acceptance factors of the website WEGO system to get electronic ticket. The population of this study is all of the consumers who use the website WEGO in the purchase of e-ticketing for travel services and hospitality . This study used a non-probability sampling. The sample used in this study are some consumers who had used the electronic commerce and domiciled in Indonesia. This study used data analysis Structural Equation Modeling (SEM) or Structural Equation Modeling with AMOS software version 18. This study shows that the influence of perception Pleasure to the User Satisfaction regarding the purchase insignificant because of the pleasure experienced within the consumer generally does not make the consumer stop to demand more for services provided by the company. This is what can cause the consumer is not completely satisfied even though consumers have been quite happy with the services provided. Keywords : Technology Acceptance Model (TAM), usefulness, ease of use, user satisfaction, enjoyment, security and privacy